Using metabarcoding and droplet digital PCR to investigate drivers of historical shifts in cyanobacteria from six contrasting lakes - Maïlys Picard; Xavier Pochon; Javier Atalah; John K. Pearman; Andrew Rees; Jamie D. Howarth; Christopher M. Moy; Marcus J. Vandergoes; Ian Hawes; Samiullah Khan; Susanna A. Wood (Scientific Reports, 2022)
Abstract The frequency and intensity of cyanobacterial blooms is increasing worldwide. Multiple factors are implicated, most of which are anthropogenic. New Zealand provides a useful location to study the impacts of human settlement on lake ecosystems. The first humans (Polynesians) arrived about 750 years ago. Following their settlement, there were marked landscape modifications which intensified after European settlement about 150 years ago. The aims of this study were to reconstruct cyanobacterial communities in six lakes over the last 1000 years and explore key drivers of change. Cyanobacterial environmental DNA was extracted from sediment cores and analysed using metabarcoding and droplet digital PCR. Cyanobacteria, including potentially toxic or bloom forming species, were already present in these lakes prior to human arrival, however their overall abundance was low. Total cyanobacteria abundance and richness increased in all lakes after European settlement but was very pronounced in four lakes, where bloom-forming taxa became dominant. These shifts occurred concomitant with land-use change. The catchment of one deteriorated lake is only moderately modified, thus the introduction of non-native fish is posited as the key factor driving this change. The paleolimnological approach used in this study has enabled new insights into timing and potential causes of changes in cyanobacterial communities.